TiO2 Immobilized on Manihot Carbon: Optimal Preparation and Evaluation of Its Activity in the Decomposition of Indigo Carmine - Antonio Cisneros, Cynthia Magaly; Dávila-Jiménez, Martín M.; Elizalde-González, María P.; García-Díaz, Esmeralda (International Journal of Molecular Sciences, 2015)
Applications of carbon-TiO2 materials have attracted attention in nanotechnology due to their synergic effects. We report the immobilization of TiO2 on carbon prepared from residues of the plant Manihot, commercial TiO2 and glycerol. The objective was to obtain a moderate loading of the anatase phase by preserving the carbonaceous external surface and micropores of the composite. Two preparation methods were compared, including mixing dry precursors and immobilization using a glycerol slurry. The evaluation of the micropore blocking was performed using nitrogen adsorption isotherms. The results indicated that it was possible to use Manihot residues and glycerol to prepare an anatase-containing material with a basic surface and a significant SBET value. The activities of the prepared materials were tested in a decomposition assay of indigo carmine. The TiO2/carbon eliminated nearly 100% of the dye under UV irradiation using the optimal conditions found by a Taguchi L4 orthogonal array considering the specific surface, temperature and initial concentration. The reaction was monitored by UV-Vis spectrophotometry and LC-ESI-(Qq)-TOF-MS, enabling the identification of some intermediates. No isatin-5-sulfonic acid was detected after a 60 min photocatalytic reaction, and three sulfonated aromatic amines, including 4-amino-3-hydroxybenzenesulfonic acid, 2-(2-amino-5-sulfophenyl)-2-oxoacetic acid and 2-amino-5-sulfobenzoic acid, were present in the reaction mixture.
Keywords: Carbono